The fucosylated CD147 enhances the autophagy in epithelial ovarian cancer cells - Hu, Zhenhua (Oncotarget, 2016)
Autophagy is modulated by multiple factors including CD147, but little is know about the effects and mechanism by which the modification of CD147 by Lewis y antigen regulates autophagy of ovarian cancer cell. Here, we reported that Lewis y antigen can promote basic autophagy activity and restrain autophagic cell death in ovarian cancer cells. Furthermore, human whole genome expression profile microarrays and massage pathway analysis revealed that during early stages of autophagy in ovarian cancer cells with highly expressing Lewis y antigen, PI3K/Akt-mTOR activity was reduced, in contrast, the PI3K/Akt-mTOR signaling pathway was activated as the length of amino acid deprivation increased, which inhibited eIF4G2 expression, further decreased the transcription of autophagy-related genes, suppressed autophagic cell death. we also elaborated that co-regulates protein degradation in cells via the ubiquitin-proteasome system and the autophagy-lysosome pathway. These findings suggested that the modification of CD147 by Lewis y antigen enhanced the survival ability by promoting basic autophagy activity and restraining autophagic cell death in ovarian cancer, thus playing an important role in ovarian cancer malignant progression.